The Language; his study and his teaching - Álvaro William Santiago Galvis (Corporación Universitaria Minuto de Dios, 2007)
This text talks about language and its relationship with language teaching. In which the concept of language is characterized by presenting an overall vision of some language schools; the applied linguistics current issues and, finally, it makes a reflection about the language teaching process.